ESTABLISHMENT AND SIMULATION OF OFHC COPPER CONSTITUTIVE MODEL IN MESOSCALE CUTTING PROCESS - TIAN Lu; HAN XuZhao; GAO Feng; HAN Chuang (Jixie qiangdu)
Micro-machining can produce size effect under mesoscopic scale,by using the strain gradient plasticity theory of dislocation mechanism,considering the microstructure characteristics of the material,the material constitutive model under mesoscopic scale is established,which can be used to explain the size effect of micro-machining. The material constitutive model under the mesoscopic scale derived from the theory is analyzed and studied,and the stress-strain curves and simulation results under different conditions are obtained in this article. The research shows that with the increase of cutting thickness,the stressstrain curve of the material will tend to the stress-strain curve of macro cutting. As the rake angle of the tool increases,the internal stress of the material increases accordingly,and the scale effect of the material becomes more obvious. The rake angle of the tool also has a great influence on the formation of the chip,and the smaller tool rake angle is more conducive to accumulating material and thus forming chips. The cutting edge radius of the tool is the root cause of the phenomenon of minimum cutting thickness. With the decrease of the cutting edge radius,the scale effect of the material becomes more prominent.